Innovative ultrasound assisted synthesis of sponge like cerium dioxide nanostructure using Rosa Damascena extract and its efficient performance for cancer therapy - Mahnaz Amiri; Sahar Zinatloo-Ajabshir; Meysam Ahmadi-Zeidabadi; Fariborz Sharifianjazi (Scientific Reports)
Abstract In this work, cerium dioxide nanostructures were synthesized in an easy sonochemical way. CeO2 nanoparticles have received much attention in nanotechnology. CeO2NPs, exhibit biomimetic properties depending on their size, ratio of valency on their surface, and the ambient physico-chemical properties. Nanomedicine has emerged as a promising avenue for targeted cancer therapy, aiming to develop innovative approaches with improved efficacy and reduced side effects. Here, for the production of cerium dioxide nanostructures, a new and natural capping agent called Rosa Damascena extract was utilized, as well as ceric ammonium nitrate as a metal precursor. The results of the characterization of the oxide sample fabricated in the presence of Rosa Damascena extract demonstrated that nanostructures with a sponge-like morphology, which have a pure cubic crystal phase, were formed. The cytotoxicity effect of CeO2 NPs on glioblastoma and neuroblastoma cell lines (T98, SHSY5Y) was studied using the MTT test; cerium oxide nanoparticles exhibited cytotoxicity effects on T98 and SHSY5Y cell lines, compared to the control. The improved cytotoxic effects can be due to the plant secondary metabolites involved in the green synthesis of NPs. Consequently, synthesized CeO2 NPs have revealed an acceptable inhibitory impact upon cancer cell lines.